Treatment of Advanced Hepatocellular Carcinoma after Failure of Sorafenib Treatment: Subsequent or Additional Treatment Interventions Contribute to Prolonged Survival Postprogression - Masaaki Kondo; Kazushi Numata; Koji Hara; Akito Nozaki; Hiroyuki Fukuda; Makoto Chuma; Shin Maeda; Katsuaki Tanaka (Gastroenterology Research and Practice)
Background. Sorafenib is a first-line treatment option for advanced hepatocellular carcinoma (HCC) patients; however, survival predictors upon progression have not been well characterized. In the present study, we aimed to show the efficacy of multidisciplinary therapy for patients who had failed to respond to sorafenib treatment. Methods. Among 146 BCLC stage B or C HCC patients treated with sorafenib monotherapy between July 2009 and August 2014, the first radiological progression according to the modified RECIST was identified in 71 patients; factors predicting overall survival (OS) and survival postprogression (SPP) were analyzed in these patients. Results. The median OS and SPP for patients who failed to respond to sorafenib treatment were 10.5 and 6.2 months, respectively, and the SPP was strongly correlated with the OS (r=0.982, P<0.01, and R2=0.965). The independent predictors of OS and SPP were identical. The predictors of SPP were des-gamma-carboxy prothrombin, progression of portal vein thrombosis, and subsequent second-line or additional treatment. Conclusions. SPP is closely associated with OS and might be notable in patients who have failed to respond to initial sorafenib treatment. Furthermore, interventions consisting of other treatment options upon the appearance of progression might prolong OS.